Introduction to Strength Training for the Performance of Galaxy Aquatic Club Athletes - Imam Sugeng; Arika Umi Zar'in; Ari Setiawan; Nurul Afifah (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2026)
Swimming is one of the sports that demands total physical fitness, including endurance, flexibility, technique, and muscular strength. However, strength training (strength training) as an integral part of the training program for swimmers has not been widely applied, especially at the club level in Indonesia. This community service activity aims to introduce the concept and practice of strength training to athletes at Club Galaxy Aquatic, Kediri. The method used is participatory action in the form of educational socialization, practical demonstrations, and mentored exercises for 8 weeks with a frequency of 2 sessions per week. The results show that after the introduction and implementation of the strength training program, there was a significant improvement in athletes' physical condition indicators, particularly upper body strength, core stability, and 50-meter freestyle swimming performance. Athletes and coaches also showed increased understanding of the importance of integrating strength training into swimming training programs. This activity proves that structured strength training introduction can have a positive impact on the performance of young swimmers